2004
DOI: 10.1007/s11199-004-5465-5
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Self-Perceptions of Young Women Experiencing Abuse in Dating Relationships

Abstract: Though information about one's sexuality may be inferred from sexual interactions themselves, a sexual sense of self may also be derived from the quality of the intimate relationship more generally. In this study, we examined the sexual self-perceptions of young women in dating relationships (N = 108) as a function of whether these relationships were characterized by abuse. Negative sexual self-perceptions were found to be more evident among women who were experiencing physical/psychological abuse or sexual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
3
18
0
2
Order By: Relevance
“…Prior studies have found support for negative sexual self-perceptions among CSA survivors that encompass qualities such as guilt regarding sexual activities and feelings (Walser & Kern, 1996), perceptions of self as promiscuous (Fromuth, 1986), views of sexuality in hostile terms (Schloredt & Heiman, 2003), and feeling as if sex is bad and dirty due to the abuse events and messages received from the perpetrator (Maltz, 1991). In addition, negative sexual self-perceptions have been associated with physical and psychological abuse as well as sexual coercion in adult intimate relationships (Offman & Matheson, 2004). The discrepancies between these findings and those of previous studies examining the sexual selfschemas of CSA survivors call into question the content validity of the Sexual Self-Schema Scale for CSA survivors.…”
Section: Introductionmentioning
confidence: 82%
“…Prior studies have found support for negative sexual self-perceptions among CSA survivors that encompass qualities such as guilt regarding sexual activities and feelings (Walser & Kern, 1996), perceptions of self as promiscuous (Fromuth, 1986), views of sexuality in hostile terms (Schloredt & Heiman, 2003), and feeling as if sex is bad and dirty due to the abuse events and messages received from the perpetrator (Maltz, 1991). In addition, negative sexual self-perceptions have been associated with physical and psychological abuse as well as sexual coercion in adult intimate relationships (Offman & Matheson, 2004). The discrepancies between these findings and those of previous studies examining the sexual selfschemas of CSA survivors call into question the content validity of the Sexual Self-Schema Scale for CSA survivors.…”
Section: Introductionmentioning
confidence: 82%
“…They were less satisfied with their relationships as well. Similarly, Offman and Matheson (2004) reported that women in physically or psychologically abusive or sexually coercive relationships, compared to women who were not, were more depressed and had more negative sexual selfperceptions. Last, women who experienced psychological aggression from men in dating relationships were more likely to express bulimic symptoms and attempt to diet (Skomorovsky et al 2006).…”
Section: Interpersonal Scriptsmentioning
confidence: 98%
“…Indeed, research has documented that victims experience reactions ranging from moderately upsetting to extremely distressing. Adjustment difficulties such as depression, anxiety, low self-esteem, and negative sexual self-perceptions (De Visser, Rissel, Richters, & Smith, 2007;Offman & Matheson, 2004) often prevent victims from functioning adequately in their day-to-day lives and engaging in healthy interpersonal relationships. These significant repercussions underscore the need to broaden our understanding of the actual frequency of SC and its impact.…”
Section: Introductionmentioning
confidence: 99%